A Methodological Safe-by-Design Approach for the Development of Nanomedicines - Schmutz, Mélanie; Borges, Olga; Jesus, Sandra; Borchard, Gerrit; Perale, Giuseppe; Zinn, Manfred; Sips, Ädrienne A. J. A. M; Soeteman-Hernandez, Lya G.; Wick, Peter; Som, Claudia (Frontiers in Bioengineering and Biotechnology, 2020)
Safe-by-Design (SbD) concepts foresee the risk identification and reduction as well as uncertainties regarding human health and environmental safety in early stages of product development. The EU’s NANoREG project and further on the H2020 ProSafe initiative, NanoReg2 and CALIBRATE projects have developed a general SbD approach for nanotechnologies (e.g. paints, textiles, etc.). Based on it, the GoNanoBioMat project elaborated a methodological SbD approach (GoNanoBioMat SbD approach) for nanomedicines with a focus on polymeric nanobiomaterials (NBMs) used for drug delivery. NBMs have various advantages such as the potential to increase drug efficacy and bioavailability. However, the nanoscale brings new challenges to product design, manufacturing and handling. Nanomedicines are costly and require the combination of knowledge from several fields. In this paper, we present the GoNanoBioMat SbD approach, which allows identifying and addressing the relevant safety aspects to address when developing polymeric NBMs during design, characterization, assessment of human health and environmental risk, manufacturing and handling and combines the nanoscale and medicine field under one approach. Furthermore, regulatory requirements are integrated into the innovation process.